2020
DOI: 10.1002/jcp.29754
|View full text |Cite
|
Sign up to set email alerts
|

Emerging landscape of circular RNAs as biomarkers and pivotal regulators in osteosarcoma

Abstract: Osteosarcoma represents the most prevailing primary bone tumor and the third most common cancer in children and adolescents worldwide. Among noncoding RNAs, circular RNAs (circRNAs) refer to a unique class in the shape of a covalently closed continuous loop with neither 5′ caps nor 3′‐polyadenylated tails, which are generated through back‐splicing. Recently, with the development of whole‐genome and transcriptome sequencing technologies, a growing number of circRNAs have been found aberrantly expressed in multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 157 publications
0
26
0
Order By: Relevance
“…Meanwhile, histone methyltransferase has been discovered to regulate the chemosensitivity in OS ( Jiang et al, 2018 ; He et al, 2019 ). Additionally, potential roles of multiple ncRNAs also have been validated in OS, such as the circRNA ( Tu et al, 2020 ) and lncRNA ( Ren et al, 2020 ; Xu et al, 2020 ). Li X. et al (2017) reported that HOX transcript antisense intergenic RNA (HOTAIR) could enhance the development of OS via DNA methylation of CDKN2A gene.…”
Section: Roles Of M 6 a In Musculoskeletal Disordementioning
confidence: 99%
“…Meanwhile, histone methyltransferase has been discovered to regulate the chemosensitivity in OS ( Jiang et al, 2018 ; He et al, 2019 ). Additionally, potential roles of multiple ncRNAs also have been validated in OS, such as the circRNA ( Tu et al, 2020 ) and lncRNA ( Ren et al, 2020 ; Xu et al, 2020 ). Li X. et al (2017) reported that HOX transcript antisense intergenic RNA (HOTAIR) could enhance the development of OS via DNA methylation of CDKN2A gene.…”
Section: Roles Of M 6 a In Musculoskeletal Disordementioning
confidence: 99%
“…High-throughput omics analysis has increasingly applied to osteosarcoma with the rapid innovating of sequencing technology and bioinformatics (Zhao et al, 2020). Researchers aim to use these techniques to discover the causes of tumorigenesis (Mirabello et al, 2020), metastasis (Xie et al, 2018), drug resistance (Zhu et al, 2019), and other disease processes, and to identify prognostic biomarkers (Zhang et al, 2019;Feng et al, 2020;Tu et al, 2020). Since James P. Allison and Tasuku Honjo shared the 2018 Nobel Prize in Physiology or Medicine for discovering a cancer cure via the suppression of negative immune regulation (The Nobel Prize, 2020), research and applications of TIIC in tumors have reached a new climax.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, circRNAs were regarded as transcriptional noises produced during abnormal splicing. Currently, with the application of high-throughput RNA sequencing (RNAseq) in biological study, thousands of circRNAs have been newly identified and even functionally annotated in multiple physiological and pathological processes of eukaryotes, such as the progression of carcinoma [19,20], inflammation [21], aging [22], infection [23], etc.…”
Section: Introductionmentioning
confidence: 99%